2010
DOI: 10.1161/circulationaha.108.808071
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Support by Left Ventricular Assist Devices Reduces Cardiomyocyte DNA Content in the Failing Human Heart

Abstract: Background-Whether adult cardiomyocytes have the capacity to regenerate in response to injury and, if so, to what extent are still issues of intense debate. In human heart failure, cardiomyocytes harbor a polyploid genome. A unique opportunity to study the mechanism of polyploidization is provided through the setting of hemodynamic support by left ventricular assist devices. Hence, the cardiomyocyte DNA content, nuclear morphology, and number of nuclei per cell were assessed before and after left ventricular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 27 publications
0
43
3
2
Order By: Relevance
“…This highlighted the intercalated disks and allowed discrimination of longitudinal margins, as previously described. 17 The extent of myocardial fibrosis was determined on sequential LV sections stained with 0.1% picrosirius red. 11 LV expression of connective tissue growth factor (CTGF) protein was examined by immunohistochemistry (antibody from Abcam, Cambridge, United Kingdom).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…This highlighted the intercalated disks and allowed discrimination of longitudinal margins, as previously described. 17 The extent of myocardial fibrosis was determined on sequential LV sections stained with 0.1% picrosirius red. 11 LV expression of connective tissue growth factor (CTGF) protein was examined by immunohistochemistry (antibody from Abcam, Cambridge, United Kingdom).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…VAD are also used to reduce ventricular load with the objective of enhancing the ability of the ventricle to support a greater load, i.e., to "rest" or re-train the ventricle of patients with dilated cardiomyopathy (CMP), even restoring function to the point of enabling pump removal (Birks et al, 2011). It is conceivable that the use of VAD may increase cardiomyocyte number, and evidence of this comes from recent prospective studies of myocardial biopsies showing an increased number of diploid myocytes in end stage congestive heart failure patients supported as a bridge to transplant with LVAD (Wohlschlaeger et al, 2010). Manginas (Manginas et al, 2009) has shown that endothelial progenitor cells are also mobilized by VAD use in patients.…”
Section: (Pre-) Failing Fontan Rescue Via Activation-rv Strengtheningmentioning
confidence: 99%
“…Abb. 4a "inset") nach LVAD könnte auf Fusion präexistenter Kardiomyozyten mit proliferierten Stammzellen hinweisen [43].…”
Section: Veränderungen Des Kardiomyozytären Dna-gehaltsunclassified